Gender Influence on the Organizational Silence in the School Sector in Amman, Jordan. - MOHAMMED AL ZOUBI, MUNIF; KHALED ALKHLAIFAT, OSAMA (International Journal of Psychosocial Rehabilitation, 2024)
This research is based on the the school sector in the Jordanian Capital Amman andaims to measure the difference in the silence level between teachers according togender and to determine which silence's factors have an impact on the decision-makingprocess. A questionnaire was distributed to collect the information needed from a studysample of 1643 male and female teachers that were randomly selected. The requiredtests were carried out to ensure the reliability of the questionnaire. Furthermore, thecorrelation coefficient and multiple regression analysis was used to test the hypothesesof the study. According to some of the results there was a moderate difference in thesilence level between genders, and there was an inverse relationship between thefactors of silence and participation in decision-making. Moreover, the results showedthat the organizational silence level is higher in female teachers than in male ones.Furthermore, the results showed that female teachers are higher in each silence factorexcept for psychological withdrawal